Investigating the Added Value of the EQ-5D-5L With Two Bolt-On Items in Patients With Hemophilia - Xu, Richard Huan; Dong, Dong; Luo, Nan; Yang, Renchi; Liu, Junshuai; Zhang, Shuyang (Frontiers in Medicine, 2021)
Objective: This study examined the impact of adding two condition-specific bolt-on items to the EQ-5D-5L and assessed their psychometric properties in patients with hemophilia. Methods: The data were obtained from a nationwide cross-sectional online survey of patients with hemophilia in China. Self-reported and proxy-reported data were analyzed separately. Ceiling effect, informativity, and discriminatory power of the EQ-5D-5L with two bolt-on items, dignity (DG), and bleeding (BL), were examined. Spearman's rank correlation (rho) was used to assess the associations of the EQ-5D-5L and two bolt-on items with the Hemophilia Quality of Life Questionnaire for Adults (Haem-A-QoL) and SF-12. Multiple regression analysis was performed to evaluate the explained variance of the EQ-5D-5L and bolt-on items in predicting EQ-VAS scores. Results: A total of 895 patients and 222 caregivers completed the questionnaire. The ceiling effect decreased from 1.9 to 0.6% and 5.9 to 0.9% when using the EQ-5D-5L and the EQ-5D-5L with two bolt-on items among participants with both self- and proxy-completed questionnaires. Both DG and BL were strongly correlated with Haem-A-QoL sum score [rho: DG = 0.64 (patient) vs. 0.66(proxy); BL = 0.49 (patient) vs. 0.31 (proxy)], SF-12 mental component [rho: DG = −0.36 (patient) vs. −0.41 (proxy); BL = −0.53 (patient) vs. −0.57(proxy)], and SF-12 physical component [rho: DG = −0.61 (patient) vs. −0.61 (proxy); BL = −0.35 (patient) vs. −0.39 (proxy)]. Known-group comparisons confirmed that the two bolt-on items had satisfactory discriminatory power. Multiple regression analysis indicated that adding two bolt-on items significantly increased the ability to predict EQ-VAS scores. The adjusted R2 increased by 8.2 and 8.8% for reports completed by the patients or patients' proxy respondents, respectively. Conclusion: Adding the DG and BL bolt-on items can increase performance on the EQ-5D-5L in patients with hemophilia. A future valuation study will be carried out.